Intravascular lithotripsy vs. rotational atherectomy on coronary microcirculation: a retrospective multicenter propensity-matched multicenter study - Xi Zhang; Xi Zhang; Xi Zhang; Peijian Wang; Chenguang Li; Tao Zhao; Tao Zhao; Tao Zhao; Jiaji He; Jiaji He; Jiaji He; Bin Liu; et al. (Frontiers in Cardiovascular Medicine)
BackgroundCoronary microvascular dysfunction (CMD) predicts poor prognosis in patients with coronary artery disease (CAD). However, the impact of intravascular lithotripsy (IVL) on CMD remains unclear, and no studies have directly compared IVL and rotational atherectomy (RA) in the context of CMD.ObjectiveThis study aimed to evaluate CMD, as indicated by angiographic microvascular resistance (AMR), in patients undergoing IVL- or RA-assisted PCI for heavily calcified coronary lesions.MethodsThis multicenter retrospective cohort study enrolled patients underwent either RA- or IVL-assisted percutaneous coronary intervention (PCI) at three centers. Propensity score matching (1:2) was performed to control for potential bias. The primary outcomes included the post-PCI AMR values and CMD incidence. The secondary outcomes included peri-procedural adverse events (PPAEs).ResultsA total of 377 patients were registered, and 210 propensity-matched patients (140 RA vs. 70 IVL) were analyzed. Pre-PCI AMR was similar between the groups (RA 1.24 ± 0.53 vs. IVL 1.28 ± 0.50, p = 0.615). Following PCI, AMR was significantly higher in the RA group compared to IVL (2.43 ± 0.35 vs. 2.26 ± 0.50, p = 0.015), while CMD incidence was comparable (RA 32.9% vs. IVL 27.1%, p = 0.398). In addition, the PPAEs rates were lower in the IVL group but the difference showed no statistical significance (27.9% vs. 17.1%, p = 0.088).ConclusionsIVL demonstrates less microvascular dysfunction compared to RA, as indicated by lower post-PCI AMR. These findings suggest that IVL may offer advantages in preserving coronary microvascular function across various clinical scenarios when both techniques are equally available and applicable, but further large-scale prospective studies are needed to verify these results.